2019
DOI: 10.1002/ejic.201900344
|View full text |Cite
|
Sign up to set email alerts
|

A Precious Catalyst: Rhodium‐Catalyzed Formic Acid Dehydrogenation in Water

Abstract: The performance of rhodium complex [Cp*Rh(bis-(pyrazol-1-yl)methane)Cl]Cl was evaluated for formic acid dehydrogenation in aqueous solution. Solid-state X-ray diffraction helped to confirm the catalyst structure. Multinuclear NMR spectroscopy was employed to follow the dehydrogenation of formic acid. The reactions have been carried out in high- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…The possibility of a hydrated proton being the proton source has been proposed by Himeda and co-workers in their experimental report . Recently, Fink and Laurenczy have also suggested that H 3 O + could be the proton source for liberating H 2 gas in their recent report on FAD catalyzed by a Rh complex . Computational studies by Surawatanawong et al and Liu et al also demonstrate that hydronium ion is the proton source for protonation of metal-hydride bond to produce molecular hydrogen in their case as well.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The possibility of a hydrated proton being the proton source has been proposed by Himeda and co-workers in their experimental report . Recently, Fink and Laurenczy have also suggested that H 3 O + could be the proton source for liberating H 2 gas in their recent report on FAD catalyzed by a Rh complex . Computational studies by Surawatanawong et al and Liu et al also demonstrate that hydronium ion is the proton source for protonation of metal-hydride bond to produce molecular hydrogen in their case as well.…”
Section: Resultsmentioning
confidence: 90%
“…28 Recently, Fink and Laurenczy have also suggested that H 3 O + could be the proton source for liberating H 2 gas in their recent report on FAD catalyzed by a Rh complex. 54 Computational studies by Surawatanawong et al 55 and Liu et al 56 also demonstrate that hydronium ion is the proton source for protonation of metal-hydride bond to produce molecular hydrogen in their case as well. Thus, the possibility of protonation by hydronium ion was also considered for investigation in this work.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the metallocycle adopts a distorted boat conformation with a dihedral angle of 27.4(1)°between the N1-N2-N3-N4 and N1-Rh1-N4 planes. Upon coordination of the ligand, the dihedral angle between the pyrazolyl rings significantly decreased from 72.8(2)-73.06(9)°(observed in the free ligand [13,14]) to 56.85(9)°. All bond distances and angles were found to be in agreement with closely related complexes reported in the literature [15][16][17].…”
Section: Commentmentioning
confidence: 97%
“…The catalytic dehydrogenation of FA has been extensively studied during the past decade. Several homogeneous complexes, based on noble metals such as iridium, rhodium, molybdenum, ruthenium, and osmium, have been reported as catalysts for this reaction. These studies demonstrated that the ligand architecture has a crucial effect on the catalyst activity and stability and therefore governs the catalyst turnover number (TON) and turnover frequency (TOF).…”
mentioning
confidence: 99%